Cardiopulmonary Exercise Testing in Patients with Implantable Cardioverter-Defibrillator: A Retrospective Study - Mizzaci,Carolina (2019)
Abstract Background: Cardiopulmonary exercise testing is widely used in the evaluation of patients with left ventricular dysfunction, and some of these patients have an implantable cardioverter-defibrillator (ICD). However, this test presents specific challenges because of the susceptibility to ventricular arrhythmias during maximal levels of exercise. Objective: To evaluate the safety of cardiopulmonary exercise testing in patients with ICD. Methods: The study included patients with ICD who underwent cardiopulmonary exercise testing between 2007 and 2015. The tests were completed once the electronic devices were programmed. The maximum allowed heart rate reached during exercise was 10 beats below the first therapy zone programmed. Results: The study included 69 patients with mean age 53.7 ± 10.8 years, including 68% men. Exercise time was 8.7±2.3 minutes, with peak oxygen consumption of 13.3 ± 4.3 ml.kg-1.min-1. Peak heart rate was 62.9 ± 13.4% of the maximum rate predicted, with all patients taking specific medication. Ventricular arrhythmia was observed in 29% of the patients, and paired ventricular extrasystoles, ventricular bigeminism or non-sustained ventricular tachycardia were observed in only 14.5% of the patients. There was no sustained ventricular arrhythmia resulting in ICD therapy or other complications, such as inappropriate therapies. The frequency of severe events was 0%, 95% CI (0 - 5.2%). Conclusion: In the sample of patients evaluated, the cardiopulmonary exercise testing was shown to be safe during its performance in a hospital setting, following the safety standards.